Merry-Go-Round - Shepard, David (image Entertainment, 2003)
For his fourth film "Merry-Go-Round" Erich von Stroheim suffered a new kind of humiliation; he was fired. According to historians, Stroheim finished about 14 minutes of footage that are actually incorporated into the 110-minute final product. Director Rupert Julian took over and received sole credit, re-writing Stroheim's script and softening its edges. Still, the usual Stroheim touches are there: in pre-war Vienna, a womanizing count who wears a uniform and sports Stroheim's pointy haircut meets and falls in love with a carnival organ-grinder on the eve of his wedding. Stroheim's original scenes stand out: the count's fiancée smoking a cigar, a dog enjoying the count's bathwater, and a raucous party with a semi-naked girl jumping out of a punch bowl. [www.combustiblecelluloid.com]